Tall Buildings in Urban Context: Planning Indicators for Tall Buildings in the Urban Context (Journal of University of Babylon for Engineering Sciences, 2018)
The tall buildings play an important role in giving a distinctive image for the city. It is one of the most important features of the big cities, as it enhances its value and reflects its urban economic and technological development, as well as the city's image for the local and the international levels. If they have been designed and planned well in its urban context. The tall buildings contribute to create a vibrant, prosperous, sustainable and attractive city for living and working, farther more optimize the energy and land use, providing public spaces, streets and spaces of social interaction as well as employing high technology, especially in infrastructure.The research adopted the tall buildings in the urban context as a general concept. The multiple contemporary trends of planning considerations for tall buildings in the urban context and the lack of a comprehensive picture resulted the special concept of the search "Tall buildings in the urban context ". Which was done by reviewing several international, Arabic and local studies for identifying the knowledge gap that led to the emergence of a research problem in terms of the multiplicity and diversity of planning aspects. Most of the international studies indicated them in general and selective, while the thesis was implicit and unclear in the Arab studies, and there were lack in local studies. The research problem, which focused on the most critical aspects of the previous studies, was characterized by the lack of comprehensive knowledge of the planning and designing indicators of the tall buildings relationship with the urban context and the local reality. For that objective goal of the research determined to provide the most comprehensive and clear knowledge of the planning and designing indicators of tall buildings in the urban context and in particular the local reality. The achievement of this goal necessitated the adoption of a descriptive analytical approach to the relevant studies and practical experiments within the structure of a sequence of basic steps for research. The first step was to construct a comprehensive theoretical framework that defines tall buildings in urban context. That resulted three aspects: general analytical aspects of tall buildings, planning considerations for tall buildings in the urban context، the second step focused on applying the concepts of the theoretical framework to selected models of local projects and analyzed them then discussion the results of the practical study, after that presenting the conclusions of the application within the local reality.